APLIKASIPROGRAM TOPOCAD UNTUK PENGGAMBARAN HASIL UKUR TANAH - Afif Nofarida, Sunar Rochmadi (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT Construction works need various drawings, including the drawings of earth surface profiles used to prepare plan and design of construction works. If the drawing process of earth surface profile is conducted manually, it will take relatively longer time. Using Topocad program it is hoped to produce high precission earth surface profiles. This research aims to prove that the drawing process is more effective and efficient using Topocad computer program. This research was conducted using the Football Field Replacement Development Project in Dusun Kayen, Desa Sinduadi, Kecamatan Mlati, Kabupaten Sleman, Yogyakarta. The field measurement was conducted to gather data used to calculate distance and height difference between points. The data were processed in the Surveying Laboratory, FaCUlty of Engineering, UN~ Based on data analysis, it is concluded that the calculation process of surveying data is more effective and efficient supported by Microsoft Excel software. Applying Topocad program using the surveying data results single cross sections, multiple cross section, single long section, polygon and cross section detail were drawn digitally. The drawings produced utiliZing Topocad program are easy to be edited and therefore should be suitable for planning and designing civil construction works, because the drawings are in the environment of the AutoCAD software. Key words: Earth surface~ profile, computer aided drawing, surveying drawing.